Neonatal Magnesium Levels Correlate with Motor Outcomes in Premature Infants: A Long-Term Retrospective Cohort Study - Doll, Elizabeth; Wilkes, Jacob; Cook, Lawrence J.; Korgenski, E. Kent; Faix, Roger G.; Yoder, Bradley A.; Srivastava, Rajendu; Sherwin, Catherine M. T.; Spigarelli, Michael G.; Clark, Erin A. S.; Bonkowsky, Joshua L. (Frontiers in Pediatrics, 2014)
Objective Chronic neurological deficits are a significant complication of preterm birth. Magnesium supplementation has been suggested to have neuroprotective function in the developing brain. Our objective was to determine whether higher neonatal serum magnesium levels were associated with better long-term neurodevelopmental outcomes in very low birth weight infants. Study Design A retrospective cohort of 75 preterm infants (<1500 g, gestational age <27 weeks) had follow-up for the outcomes of abnormal motor exam and for epilepsy. Average total serum magnesium level in the neonate during the period of prematurity was the main independent variable assessed, tested using a Wilcoxon rank-sum test. Results Higher average serum magnesium level was associated with a statistically significant decreased risk for abnormal motor exam (p 0.037). A lower risk for epilepsy in the group with higher magnesium level did not reach statistical significance (p 0.06). Conclusion This study demonstrates a correlation between higher neonatal magnesium levels and decreased risk for long-term abnormal motor exam. Larger studies are needed to evaluate the hypothesis that higher neonatal magnesium levels can improve long-term neurodevelopmental outcomes.